Community-Based Rehabilitation Program of Drug Surrenderees in the Municipality of Lingayen - Pescador, Evangeline (Southeast Asian Journal of Science and Technology, 2018)
Community-based rehabilitation is a beneficial treatment of addiction as it provides opportunities to learn how addiction settles into a healthy mind and body and how it can be beleaguered. The Municipality of Lingayen, Province of Pangasinan designed a community-based rehabilitation program to cater the health needs of drug surrenderees under the government program “TOKHANG”. It was conceptualized in 2017 and implemented by the Municipal Anti Drug Abuse Council of the LGU. No visible impact was identified hence the proponent undertook this study to assess its effectiveness for possible enhancement. Qualitative method was utilized where focus group discussion, key informant interview and observation were employed where thematic strategy were utilized in data analysis. There was an improvement noted to wellness of the surrenderees after the implementation of the said program. Moreover, the program contributed best to the peace and order of the community, strong family relationship and to the health and safety of the surrenderees. On the other hand, four significant areas were considered to enhance the program and strong support of stakeholders is vital. Indeed, high satisfaction with the program was noted